Окалиностійкість середньовуглецевих сталей в агресивних середовищах залежно від вмісту в них хрому та алюмінію - Ямшинський, М. М.; Федоров, Г. Є. (Physico-technological Institute of Metals and Alloys, 2023)
The analysis of operating conditions of heat-resistant cast parts has revealed that a necessary condition for reducing the use of metal for formation of oxide scales on their surfaces is the formation of a solid film with low electrical conductivity and high elasticity of oxide dissociation. Modern theories of alloying do not provide a complete answer to the questions posed. The oxidation theories that exist today have significant assumptions and make it impossible to create comprehensive grounded theories of heat-resistant alloying. To achieve this goal, the influence of the main alloying elements of chromium and aluminum on the heat resistance of alloys based on iron in superheated air with the addition of water vapor and carbon dioxide was investigated. The main chemical element in steels of this class is carbon, which has a negative impact on the resistance, so this fact must be taken into account when choosing heat resistant steel for the manufacture of products that work in high temperatures and corrosive environments. It is found that the additional alloying of chromium steels with aluminum significantly improves their hardness – the use of metal for the formation of scale in conditions of high temperatures and overheated air significantly reduces, but over time, the surface layer of metal becomes depleted in aluminum, since it is used for formation of its own oxide. It is found that the increase of the steam content in the air up to 25 % (by volume) three times reduces the hardness of steel with the formation of porous oxide scale, which almost entirely separates from the surface of the product due to the increase of the content of oxide and iron oxide, which intensifies the process of formation of scale and shortening its operation term. With increasing concentration of aluminum in steel up to 6 % of its scale resistance increases more than twice, and the maximum rate of "burning" of aluminum occurs if its content in steel is up to 3 % during the intensive formation of the protective film together with chromium. Therefore, the hardness of medium-carbon (0.25–0.35 % C) heat-resistant alloys based on iron is determined by the content of the basic alloying elements and the technological processes of their manufacture, which are optimal for the specific operating conditions of the products.